How Do the Political Connections and the Corporate Governance Mechanisms Affect the Firm Risk of Chinese Dual-listed Companies? - Wing Kwong Chan,; Ei Yet Chu, (Asian Academy of Management Journal of Accounting and Finance, 2024)
This research aims to assess the influences of political connections and corporate governance (CG) mechanisms on the firm risk of Chinese dual-listed companies (CDLC). CDLCs are Chinese companies that have core businesses in China and simultaneously list their shares in the Hong Kong and the China A-share markets. One hundred CDLCs are chosen for this research from 2003 to 2019. A binary variable of state control firm attribute (SCFA) is created to proxy the political connections to the Chinese government. The standard deviation of daily stock return and the mean of the natural logarithm of squared daily stock return are the two proxies of firm risk. The regression results show that the SCFA negatively influences the firm risk. Thus, the political connections, proxied by the SCFA, mitigate the firm risk. However, the state ownership’s influence on firm risk is insignificant. The regression results are supportive of our argument that SCFA and state ownership are two distinct concepts. Both the board size and independent director ratio insignificantly influence the firm risk. The CEO duality cannot be concluded to positively influences the firm risk and is not a destabilising factor in CDLCs. Evidence of the legal bonding effect is not observed in this research.